Identification of learning difficulties and misconceptions of chemical bonding material: A review - Widarti, Hayuni Retno; Nuriyanti, Dian; Sari, Meyga Evi Ferama; Wiyarsi, Antuni; Yamtinah, Sri; Rokhim, Deni Ainur (Eclética Química, 2024)
Chemical bonds are one of the materials in chemistry that are abstract in nature so that many students have difficulty learning chemical bonding material. This study aims to identify the learning difficulties frequently faced by students in understanding chemical bonding materials and various misconceptions that commonly occur in their understanding. Data collection was carried out using a systematic literature review method with several predetermined criteria. The result is that the learning difficulties experienced by students are caused by many factors, one of which is conceptual error or misconception. At present, many methods have been developed to identify students’ misconceptions about chemical bonding material such as diagnostic tests such as two-tier, three-tier and four-tier diagnostics.